A multifunctional natural treasure based on a “one stone, many birds” strategy for designing health-promoting applications: Tordylium apulum - EMRE, GİZEM (My University, 2024)
Wild plants provide important bioactive compounds, and their analysis relies heavily on selecting the right extraction techniques and solvents. This study was conducted to determine the phenolic content and biopharmaceutical potential of four different extracts (ethyl acetate, ethanol, 70% ethanol, and water) from the aerial parts of wild plant Tordylium apulum L. The biochemical profile of the extract was screened using high performance liquid chromatography -mass spectrometry (HPLC-MS) analysis. The total phenolic and flavonoid content was examined using the Folin-Ciocalteu assay and the aluminium trichloride assay, respectively. The antioxidant activity was evaluated through several tests, including 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), cupric reducing antioxidant capacity (CUPRAC), ferric reducing antioxidant power (FRAP), phosphomolybdenum (PBD), and metal chelating activity (MCA). Five types of enzyme inhibition activity were tested against acetylcholinesterase (AChE), butrylcholinesterase (BChE), tyrosinase, α-amylase, and α-glucosidase. Additionally, For the first time, the inhibitory activity of T. apulum extract against human carbonic anhydrase isoenzymes I and II (hCA-I and hCA-II) was evaluated. Fifty-five compounds for negative ionization mode, and twenty-eight compounds for positive ionization mode were recorded in HPLC-MS analysis and they were polyphenolic, flavonoids, carbohydrates, sugar alcohol and amino acids. These results indicate that different solvents extract varying levels of antioxidants from T. apulum, with ethanol and water extracts generally exhibiting superior antioxidant activities. The ethanol extract of T. apulum exhibited the maximum contents of total phenolics measuring 33.71 mg gallic acid equivalent (GAE)/g. The ethanol extract exhibited the highest inhibition of AChE with 2.28 mg galanthamine equivalent (GALAE)/g. The ethyl acetate and ethanol extracts also showed the highest hCA-I and hCA-II inhibition potential, respectively. The ethanol-water and water extracts acted on the biofilm of E. coli (49.93% and 45.22%, respectively), and the biofilm of P. aeruginosa (50.68% and 44.46%, respectively). The extracts were tested on different cell lines for cytotoxic potentials and in particular the water extract induced the apoptotic pathways in cervical cancer (HELA) cell lines. In conclusion, T. apulum exhibit multidirectional biological properties and it could be considered as a versatile agent for the development of health-promoting applications.
Keywords: Tarımsal Bilimler; Ziraat; Gıda Mühendisliği; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Food Engineering; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Engineering and Technology; Tarım Ve Çevre Bilimleri (Age); Yaşam Bilimleri (Life); Tarım Bilimleri; Moleküler Biyoloji Ve Genetik; Gıda Bilimi Ve Teknolojisi; Biyokimya Ve Moleküler Biyoloji; Agriculture & Environment Sciences (Age); Life Sciences (Life); Molecular Biology & Genetics; Food Science & Technology; Biochemistry & Molecular Biology; Yemek bilimi; Biyokimya; Food Science; Biochemistry; Anti-biofilm; Apoptosis; Carbonic anhydrase; Diabetes mellitus; Tordylium apulum; Versatile agents